Mediastinal Tumor Thymoma Type B1 T4N2M1B Stage IVB with Multimodality Therapy - Muhammad Zakki Al-Fajri; Sabrina Ermayanti; Afriani Afriani (Faculty of Mathematics and Natural Sciences (FMIPA), Universitas Negeri Padang, Indonesia, 2022)
The incidence of thymoma increases with age, generally occurs in the 40-60s. Thymoma cases are rare at a young age. The prevalence of thymoma at a young age is very small at 0.6 – 5% of all thymoma cases. Thymoma management requires multimodality therapy depending on the stage of the thymoma, along with the development of surgery, radiotherapy and chemotherapy in the past three decades. A 21-year-old male patient with complaints of shortness of breath since 5 months before being admitted to the hospital. The patient has been diagnosed with thymoma type Mediastimum Tumor Type B1 T4N2M1B stage IVB from the results of chest X-ray investigations, chest CT scan, bronchoscopy and histopathological examination. The patient has received various therapeutic modalities including 6 cycles of chemotherapy, 30 radiotherapy and thymectomy surgery